24 January 2020 Sivrice-Elazığ Earthquake: Assessment of Seismic Characteristics of Earthquake, Earthquake Territory and Structural Performance of Reinforced Concrete Structures - Dedeoğlu, İbrahim Özgür; Yetkin, Musa; Calayir, Yusuf (Sakarya University, 2022)
An earthquake with a magnitude of 6.8 (Mw) has occurred in Sivrice district of Elazığ province in Eastern Turkey, on January 24, 2020. The main shock and long-term aftershocks felt fairly by near vicinities. Many structures have been damaged severely or demolished at this moderate earthquake that occurred on East Anatolia Fault (EAF) zone. Also resulted in sum 41 casualties, including 37 people in Elazığ and 4 people in Malatya. The purpose of this paper is to give information of the tectonic characteristics of the EAF zone, the seismic characteristics of the earthquake territory, the general characteristics of the main shock and after-shocks. In addition, another purpose of this article is to reveal the damages caused by the earthquake in the reinforced concrete (RC) buildings in Elazığ, with the post-earthquake field observations. The main reasons of damages have presented and discussed. The most important reason for damages of structures is the lack of engineering services, in other words, not being constructed properly with respect to the available building codes. © 2022, Sakarya University. All rights reserved.
Keywords: 2020 Sivrice-Elazığ earthquake; damage assessment; earthquake damage survey; East Anatolia Fault zone; reinforced concrete structures